Numerical Study on the Performance of RC Slab with Protective Aluminum Foam Cladding under Near-field Explosion. Issue 3 (May 2019) - Zhang, Diandian; Yu, Runqing; Yao, Mingming; Liu, Bin
Abstract: Aluminium foam material has excellent properties and a wide application prospect in the field of protective engineering. Present study is to study the protecting effect of aluminium foam plate on RC slab. First, quasi-static compression test and SHPB test were conducted to verify the material parameters of aluminium foam with different porosity (87% and 77%). Then, the dynamic response and the failure modes of RC slabs were calculated and analysed using LS-DYNA software. The results show that the increase in the thickness of aluminium foam plate changes the failure mode of RC slabs, from the overall bending failure mode to the local spall failure mode. Reasons were discussed and some useful suggestions for design were given at last.